2017
DOI: 10.1116/1.4996139
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recrystallization and dopant activation of P+ ion-implanted super-thin Ge layers by RF hydrogen plasma treatment

Abstract: Radio-frequency (RF) hydrogen plasma treatment, thermal annealing in a furnace, and rapid thermal annealing of high-dose P+ ion implanted p-type Ge layers have been studied by Raman scattering spectroscopy, atomic force microscopy, secondary ion mass spectrometry, electrochemical capacitance-voltage profiling, four-point probes method, and x-ray reflectometry. It was shown that low-temperature RF plasma treatment at temperature about 200 degrees C resulted in full recrystallization of amorphous Ge layer implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In our previous publications it has been shown that RF plasma treatment is efficient in reducing the density of fixed positive charges in SiO 2 layers and interface traps at the Si-SiO 2 interface, [9][10][11] annealing radiation-induced and ion implantation defects in metal-insulator-semiconductor (MIS) structures, 12,13 structural ordering and recrystallization of thin amorphous semiconductor layers, 14,15 low-temperature activation of implanted doping impurities in Si and Ge. [15][16][17] In this paper, we report that low-temperature RF plasma treatment in forming gas (10%H 2 +90%N 2 ) can significantly improve the electrical characteristics of n-In 0.53 Ga 0.47 As JL MOSFETs with an Al 2 O 3 gate dielectric. In particular, it provides substantial reduction of S/D resistances, an increase of the electron mobility, resulting in the strong increase of the on-state current and transconductance, reduction of the effective positive charge in the Al 2 O 3 gate dielectric, and improvement of the subthreshold slope.…”
mentioning
confidence: 99%
“…In our previous publications it has been shown that RF plasma treatment is efficient in reducing the density of fixed positive charges in SiO 2 layers and interface traps at the Si-SiO 2 interface, [9][10][11] annealing radiation-induced and ion implantation defects in metal-insulator-semiconductor (MIS) structures, 12,13 structural ordering and recrystallization of thin amorphous semiconductor layers, 14,15 low-temperature activation of implanted doping impurities in Si and Ge. [15][16][17] In this paper, we report that low-temperature RF plasma treatment in forming gas (10%H 2 +90%N 2 ) can significantly improve the electrical characteristics of n-In 0.53 Ga 0.47 As JL MOSFETs with an Al 2 O 3 gate dielectric. In particular, it provides substantial reduction of S/D resistances, an increase of the electron mobility, resulting in the strong increase of the on-state current and transconductance, reduction of the effective positive charge in the Al 2 O 3 gate dielectric, and improvement of the subthreshold slope.…”
mentioning
confidence: 99%